The craft of information visualization : - Bederson, Benjamin B. (Morgan Kaufmann, 2003)
This book collects 38 of the key papers on information visualization from a leading and prominent research lab, the University of Marylands Human-Computer Interaction Lab (HCIL). Celebrating HCILs 20th anniversary, this book presents a coherent body of work from a respected community that has had many success stories with its research and commercial spin-offs. Each chapter contains an introduction specifically written for this volume by two leading HCI researchers, to describe the connections among those papers and reveal HCILs individual approach to developing innovations.